Pengaruh Desain Produk dan Inovasi terhadap Keputusan Pembelian Smartphone Redmi pada Masyarakat Kota Bima - Qorry Aina; Ismunandar Ismunandar (Social Science Academic, 2023)
This study titled "The Impact of Product Design and Innovation on Redmi Smartphone Purchase Decisions among Bima City Residents" investigates the relationship between product design, innovation, and purchase decisions regarding Redmi smartphones within the community of Bima City. Employing an associative research method, the study gathers data from a sample of 50 respondents using Likert-scale questionnaires. The collected data undergo validity, reliability, and classical assumption tests before being analyzed through multiple linear regression. The findings suggest that while individual product design may not significantly influence purchase decisions, innovation plays a vital role in shaping consumers' choices. When considering both factors together, the study reveals a strong correlation between product design, innovation, and purchase decisions, with a correlation coefficient of 0.768. This research highlights the considerable impact of innovation in driving consumers' preferences in the competitive smartphone market